1978
DOI: 10.1128/iai.20.3.592-599.1978
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sucrose in culture media on the location of glucosyltransferase of Streptococcus mutans and cell adherence to glass surfaces

Abstract: Streptococcus mutans strain B13 (serotype d) almost exclusively produced free glucosyltransferase (GTase) in the culture supernatant when grown in sucrosefree TTY broth medium, which was composed of Trypticase (Baltimore Biological Laboratory [BBL] Cockeysville, Md.), tryptose (Difco Laboratories, Detroit, Mich.), yeast extract (BBL), salts, and 1% glucose. Organisms grown in sucrosefree TTY broth retained very weak cell-associated GTase activity and did not adhere significantly to glass surfaces in the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

1979
1979
2000
2000

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(54 citation statements)
references
References 28 publications
1
53
0
Order By: Relevance
“…It is of interest that antibody directed against extracellular GTase significantly inhibited the cell-associated GTase activity which resulted in the marked reduction in adherence to a glass surface of viable S. mutans cells ( Table 2). It has been found that a portion of the extracellular GTase of S. mutans will bind to the surface of S. mutans cells (18,20,25,28,29), and therefore significant inhibition of GTase activity and cell adherence can be expected.…”
Section: Resultsmentioning
confidence: 99%
“…It is of interest that antibody directed against extracellular GTase significantly inhibited the cell-associated GTase activity which resulted in the marked reduction in adherence to a glass surface of viable S. mutans cells ( Table 2). It has been found that a portion of the extracellular GTase of S. mutans will bind to the surface of S. mutans cells (18,20,25,28,29), and therefore significant inhibition of GTase activity and cell adherence can be expected.…”
Section: Resultsmentioning
confidence: 99%
“…S. faecalis (Enterococcus hirae) ATCC 9790 was grown aerobically at 37 °C for 6 h in trypticase-tryptose-yeast, extract medium [10]. Cells were harvested by centrifugation and delipidated with 0.1 M sodium acetate buffer (pH 4.5)choloroform-methanol (1 : 1 : 2, v/v).…”
Section: Bacterial Strainmentioning
confidence: 99%
“…In spite of this variability, the significant correlations found between specific organisms and the polysaccharide production indicate that the floral composition may be one determining factor of the salivary enzyme activity level. The transferase activity of in vitro grown organisms is strongly influenced by ecologic factors such as growth rate and substrate availabihty (17,20). ROLLA et al (2) observed marked effects of sucrose rinses on the salivary transferase activity.…”
Section: Discussionmentioning
confidence: 99%